The Effect of Oil Price Falling on the Jordanian Economic System - Tahtamouni, Asem; Al Qaisi, Fouzan; Fendi, Usama Adnan (International Journal of Economics and Financial Issues, 2017)
Because oil is one of the most important commodities, its price impacts the economy as a whole. The oil price has dropped significantly during last years due to the growing gap between demand and supply. Jordanis a small country with a small market business and scarce natural resources, essential the government's hefty reliance on external assistance. This paper aims to evaluate the effect of oil price falling on the Jordanian economic system. Simple regression model has been used to evaluate the relationship between dependent and independent variables. It has been examined the variables between the period 2006 to 2015. The results show that the fall in oil prices impact on the Jordanian economy. While,Jordan is an importer of oil, and should be one of those countries that benefit from this drop, research has proven otherwise, in fact, the disadvantages weigh more than the advantages. Keywords: Oil Price, Jordanian Economy, Trade of Balance, Gross Domestic Product. JEL Classifications: F1, Q43